Adhesive hydrogel and composition for adhesive hydrogel production
The adhesive hydrogel, composed of polyphenol compounds and specific monomers, addresses the issue of reduced adhesion in high humidity by enhancing adhesion and resisting drying, improving electrocardiogram accuracy and simplifying production.
Patent Information
- Application Number
- JP2023117072
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-18
- Publication Date
- 2025-01-30
AI Technical Summary
Conventional hydrogels exhibit reduced adhesive strength in high humidity environments and are prone to drying, which can affect the accuracy of electrocardiogram measurements and require complex manufacturing processes.
The adhesive hydrogel is composed of polyphenol compounds, a copolymer of single-participation and crosslinked monomers, including polyglycerin with a polymerization of 10 or less, and a multi-alcohol such as triglycerin, which enhances adhesion and resistance to drying.
The hydrogel maintains high adhesion in high humidity environments and resists drying, ensuring stable contact for electrocardiogram measurements and simplifying the manufacturing process.
Smart Images

Figure 2025014484000005 
Figure 2025014484000006 
Figure 2025014484000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive hydrogel and a composition for producing an adhesive hydrogel. [Background technology]
[0002] Conventional hydrogels lose their adhesive strength in a short period of time when used in sweat or high humidity environments. It has been reported that by compounding a compound with a relatively hydrophobic structure with a hydrogel, the adhesive strength can be maintained even in high humidity environments.
[0003] For example, Patent Document 1 discloses an adhesive hydrogel including, as components, a water-soluble main chain monomer, a crosslinking agent, a polymerization initiator, and an adhesive monomer having a catechol group in the side chain. Patent Document 2 discloses a hydrogel containing a polymer matrix, water and a plasticizer, which has a plasticizer washout ratio of less than 2, a swelling ratio of 115% or less when exposed to an environment of 40°C and 90% RH for 1 hour, an initial adhesive strength to a Bakelite plate of 100 gf / 20 mm or more in an environment of 23°C and 55% RH, and a content of the plasticizer of 20 to 60% by weight relative to 100% by weight of the total amount of the hydrogel. It discloses an adhesive hydrogel whose constituent elements are a water-soluble main chain monomer, a crosslinking agent, a polymerization initiator, and an adhesive monomer having a catechol group in the side chain.
[0004] Non-Patent Document 1 discloses that a precursor hydrogel was prepared using acrylamide, carbon nanotubes, and tannic acid as a monomer, conductive filler, and adhesive, respectively, and that the precursor hydrogel was stretched and air-dried to prepare an aerogel, and that the aerogel was immersed in an aqueous tannic acid solution to obtain the desired hydrogel, and that the tannic acid significantly improved the self-adhesive strength of the hydrogel. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6663110 [Patent Document 2] Patent No. 7037639 [Non-patent literature]
[0006] [Non-Patent Document 1] J. Mater. Chem. C, 2023,11, 196-203 Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the methods of Patent Documents 1 and 2, the gel dries easily, and when used for electrocardiograms, for example, the contact between the skin and the electrodes may deteriorate, resulting in a decrease in measurement accuracy, and there is room for further improvement in usage. The method of Non-Patent Document 1 is also complicated, as it requires additional steps to make the hydrogel absorb tannic acid later. In addition, tannic acid acts as a crosslinking agent, and the adhesive effect of tannic acid is not sufficient, resulting in insufficient adhesiveness in high-temperature environments. The problem to be solved by the present invention is to provide an adhesive hydrogel that has excellent resistance to drying and has high adhesive strength even in a high humidity environment. [Means for solving the problem]
[0008] The present invention encompasses the embodiments described below. Section 1. An adhesive hydrogel comprising a polymer matrix made of a copolymer of a monofunctional monomer and a crosslinkable monomer, water, a polyhydric alcohol, and a polyphenol compound, The polyhydric alcohol contains triglycerin and / or a branched polyglycerin having a degree of polymerization of 10 or less, An adhesive hydrogel, wherein the polyphenol compound is a compound having a hydroxyl group bonded to each of two adjacent carbons forming at least one aromatic ring. Section 2. 2. The adhesive hydrogel according to claim 1, wherein the polyhydric alcohol comprises a branched polyglycerol having a degree of polymerization of 10 or less. Section 3. The adhesive hydrogel according to claim 1, wherein the monofunctional monomer comprises an acrylamide monomer. Section 4. 2. The adhesive hydrogel according to claim 1, wherein the amount of the polyphenol compound is 10 parts by mass or less per 100 parts by mass of the polymer matrix, water, and polyhydric alcohol combined. Section 5. The adhesive hydrogel of claim 1, further comprising an electrolyte. Section 6. 6. A gel sheet comprising the adhesive hydrogel according to claim 1. Section 7. Item 6. A biological electrode comprising the adhesive hydrogel according to any one of items 1 to 5. Section 8. 6. A medical external use material comprising a support and the adhesive hydrogel according to any one of items 1 to 5 provided on at least one surface of the support. Section 9. A composition for producing an adhesive hydrogel, comprising a monofunctional monomer, a crosslinkable monomer, water, a polyhydric alcohol, and a polyphenol, wherein the polyhydric alcohol comprises triglycerin and / or a branched polyglycerin having a degree of polymerization of 10 or less, and the polyphenol compound is a compound having a hydroxyl group bonded to each of two adjacent carbons forming at least one aromatic ring. [Brief description of the drawings]
[0009] [Figure 1] FIG. [Diagram 2] 1 is a schematic cross-sectional view of a medical topical agent applied to the skin. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] As used herein, "(meth)acrylate" means acrylate and / or methacrylate, "(meth)acrylic acid" refers to acrylic acid and / or methacrylic acid, "(meth)acryloyl" refers to acryloyl and / or methacryloyl, and "(meth)acrylamide" refers to acrylamide and / or methacrylamide.
[0011] As used herein, a "sheet" refers to an article having a thickness of 200 μm or more, and a "film" refers to an article having a thickness of less than 200 μm.
[0012] In this specification, the term "comprise" is a concept that encompasses "consist essentially of" and "consist only of."
[0013] In the numerical ranges described in stages in this specification, the upper or lower limit of a certain numerical range can be arbitrarily combined with the upper or lower limit of another numerical range. In addition, in the numerical ranges described in this specification, the upper or lower limit of the numerical range may be replaced with a value shown in an example or a value that can be unambiguously derived from an example. Furthermore, in this specification, a numerical value connected with "~" means a numerical range that includes the numerical values before and after "~" as the lower and upper limits.
[0014] Hereinafter, an embodiment of the present invention will be described in detail. <Adhesive hydrogel> According to one aspect of the present invention, there is provided an adhesive hydrogel comprising a polymer matrix consisting of a copolymer of a monofunctional monomer and a crosslinkable monomer, water, a polyhydric alcohol, and a polyphenol compound, wherein the polyhydric alcohol comprises triglycerin and / or a branched polyglycerin having a degree of polymerization of 10 or less, and the polyphenol compound is a compound having a hydroxyl group bonded to each of two adjacent carbons forming at least one aromatic ring.
[0015] (polymer matrix) First, the polymer matrix made of a copolymer of a monofunctional monomer and a crosslinkable monomer will be described. The monofunctional monomer may also be referred to as a polymerizable monomer. The monofunctional monomer may be a monofunctional monomer having one ethylenically unsaturated group, and is not particularly limited. (Meth)acrylamide-based monomers, (meth)acrylic acid ester-based monomers, and (meth)acrylic acid or a salt thereof are preferably used. (Meth)acrylamide-based monomers are more preferred. These monofunctional monomers may be used alone or in combination of two or more.
[0016] Examples of (meth)acrylamide monomers include N,N-dialkyl(meth)acrylamides such as (meth)acrylamide, N,N-dimethyl(meth)acrylamide, and N,N-diethyl(meth)acrylamide; N-alkyl(meth)acrylamides such as N-isopropyl(meth)acrylamide, N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, and N-propyl(meth)acrylamide; N-hydroxyalkyl(meth)acrylamides such as N-hydroxyethyl(meth)acrylamide and N-hydroxymethyl(meth)acrylamide; cationic acrylamide compounds containing amino groups such as dimethylaminopropyl(meth)acrylamide; anionic monofunctional monomers containing sulfonic acid groups such as 4-acryloylmorpholine and tert-butylacrylamidosulfonic acid, or salts thereof; and derivatives thereof. These may be used alone or in combination of two or more.
[0017] Examples of the (meth)acrylic acid ester monomer include (meth)acrylic acid alkyl esters having an alkyl group with 1 to 18 carbon atoms, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, and tert-butyl (meth)acrylate; alkoxy group-containing (meth)acrylic acid esters such as 2-methoxyethyl (meth)acrylate, ethoxyethoxyethyl (meth)acrylate, and methoxypolyethylene glycol (meth)acrylate such as methoxytriethylene glycol (meth)acrylate; hydroxyalkyl (meth)acrylates (in which an aryl group may be bonded to the hydroxyalkyl group via an ether bond) such as 2-hydroxyethyl (meth)acrylate and 2-hydroxypropyl (meth)acrylate; glycerin mono(meth)acrylate; polyalkylene glycol mono(meth)acrylate such as polyethylene glycol mono(meth)acrylate and polyethylene glycol-polypropylene glycol copolymer; and (meth)acrylic acid esters having an aromatic ring such as benzyl (meth)acrylate. These may be used alone or in combination of two or more.
[0018] Examples of (meth)acrylic acid or a salt thereof include acrylic acid, methacrylic acid, sodium acrylate, potassium acrylate, potassium methacrylate, etc. These may be used alone or in combination of two or more.
[0019] The content of the structural unit derived from the monofunctional monomer in the adhesive hydrogel of the present invention is not particularly limited, but from the viewpoint of the shape retention and flexibility of the adhesive hydrogel, it is preferably within the range of 10 to 50 parts by mass, more preferably within the range of 15 to 45 parts by mass, relative to 100 parts by mass of the total of the polymer matrix, water, and polyhydric alcohol, or relative to the total amount of the adhesive hydrogel. If the content is 10 parts by mass or more, the adhesive hydrogel has sufficient shape retention, which is preferable. Also, if the content is 50 parts by mass or less, there is little risk of impairing the flexibility of the adhesive hydrogel.
[0020] The crosslinkable monomer is not particularly limited, but is preferably a compound having two or more polymerizable carbon-carbon double bonds in the molecule, such as divinylbenzene, divinyldiphenyl, N,N'-methylenebis(meth)acrylamide, ethylene glycol di(meth)acrylate, glycerin tri(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polyglycerin di(meth)acrylate, etc. These crosslinkable monomers are preferred in terms of obtaining a hydrogel with high adhesive strength. These may be used alone or in combination of two or more. In terms of high water solubility and formation of a uniform gel, the crosslinkable monomer preferably contains a diacrylamide derivative such as N,N'-methylenebis(meth)acrylamide. When the crosslinkable monomer contains a diacrylamide derivative, the amount of the diacrylamide derivative in the crosslinkable monomer is preferably 50% by mass or more, more preferably 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, or 100% by mass.
[0021] The content of the structural unit derived from the crosslinkable monomer in the adhesive hydrogel of the present invention is not particularly limited and varies depending on the type of monofunctional monomer and crosslinkable monomer used, but from the viewpoint of shape stability and flexibility of the adhesive hydrogel, it is preferably within the range of 0.01 to 0.5 parts by mass, more preferably within the range of 0.01 to 0.1 parts by mass, relative to 100 parts by mass of the total of the polymer matrix, water, and polyhydric alcohol compound, or relative to the total amount of the adhesive hydrogel. When the content is 0.01 parts by mass or more, there is little concern about a decrease in shape stability due to low crosslink density. Also, when the content is 0.5 parts by mass or less, the gel is unlikely to become hard and brittle.
[0022] (water) The water content in the adhesive hydrogel of the present invention is not particularly limited, but in order to ensure suitable adhesive properties and electrical properties, it is preferably within the range of 10 to 60 parts by mass, more preferably within the range of 15 to 50 parts by mass, relative to the total 100 parts by mass of the polymer matrix, water, and polyhydric alcohol compound, or relative to the total amount of the adhesive hydrogel. When the water content is 10 parts by mass or more, the water content relative to the equilibrium water content of the adhesive hydrogel is not too low, and there is little risk of deterioration due to the hygroscopicity of the adhesive hydrogel. In addition, when the water content is 60 parts by mass or less, the water content relative to the equilibrium water content of the adhesive hydrogel is not too high, and there is little risk of deterioration due to drying of the adhesive hydrogel (for example, shrinkage, change in physical properties, etc.).
[0023] (Polyhydric alcohol) The polyhydric alcohol imparts moisture retention to the adhesive hydrogel, suppresses evaporation of water, and maintains the flexibility of the gel. The polyhydric alcohol contained in the adhesive hydrogel of the present invention includes triglycerin, a branched polyglycerin having a degree of polymerization of 10 or less, or both.
[0024] Triglycerin refers to a linear polyglycerin having a degree of polymerization of 3 (n=3) in the polyglycerin represented by the following formula (I).
[0025] [ka] (n is an integer equal to or greater than 1.)
[0026] By using triglycerin as a polyhydric alcohol in the adhesive hydrogel, the adhesive hydrogel can be improved in adhesive strength as well as drying resistance.
[0027] When the adhesive hydrogel of the present invention contains triglycerin, the content of triglycerin in the adhesive hydrogel is preferably within the range of 20 to 80 parts by mass, more preferably within the range of 25 to 75 parts by mass, based on 100 parts by mass of the total of the polymer matrix, water, and polyhydric alcohol compound, or based on the total amount of the adhesive hydrogel, from the viewpoint of the drying resistance of the adhesive hydrogel. When the content is 20 parts by mass or more, it is preferable in terms of the drying resistance of the adhesive hydrogel. In addition, when the content is 80 parts by mass or less, it is preferable because the viscosity of the adhesive hydrogel composition is relatively low and easy to handle.
[0028] In this specification, "branched polyglycerol" can also be called glycerol having a branched structure, and means polyglycerol that can be produced by a polyaddition reaction of glycidol. An example of the branched polyglycerol is a branched polyglycerol represented by the following formula (II). Linear polyglycerols and modified products of linear polyglycerols (e.g., polyether-added (poly)glycerol, etc.) are not included in "branched polyglycerol".
[0029] [ka]
[0030] By using a branched polyglycerin having a degree of polymerization of 10 or less as a polyhydric alcohol in the adhesive hydrogel, the adhesive strength as well as the drying resistance of the adhesive hydrogel can be improved.
[0031] In the branched polyglycerol, 50% or more of all the hydroxyl groups in the polyglycerol are preferably primary hydroxyl groups. The ratio of primary hydroxyl groups to all the hydroxyl groups contained in a specific compound is measured by a method for measuring nuclear magnetic resonance spectrum (NMR) for carbon atoms.
[0032] For example, the NMR spectrum for the carbon atoms of polyglycerol can be measured as follows. 500 mg of polyglycerin was dissolved in 2.8 mL of deuterium oxide, filtered, and then decoupled with a gate. 13 Obtain a C-NMR (125 MHz) spectrum. Note that the peak intensity indicates the presence of primary and secondary hydroxyl groups, which is proportional to the carbon number. 13 The C chemical shifts are around 63 ppm for the methylene carbon (CH2OH) and around 71 ppm for the methine carbon (CHOH), and the abundance ratio of primary hydroxyl groups to secondary hydroxyl groups is calculated by analyzing the signal intensities of these. However, the methine carbon (CHOH) representing the secondary hydroxyl group overlaps with the methylene carbon peak adjacent to the methine carbon bonded to the methylene carbon representing the primary hydroxyl group, so the integral value of itself cannot be obtained. Therefore, the integral value is calculated from the signal intensity around 74 ppm of the methylene carbon (CH2) adjacent to the methine carbon (CHOH).
[0033] The degree of polymerization of the branched polyglycerol is preferably 2 or more, more preferably 3 or more, and even more preferably 6 or more. A degree of polymerization of 3 or more is preferable because it provides a good adhesive strength improving effect. The upper limit of the degree of polymerization is preferably 10 or less. A degree of polymerization exceeding 10 is not preferable because it reduces the adhesive strength of the gel.
[0034] The number average molecular weight of the branched polyglycerol is preferably 200 to 1,000 g / mol, and more preferably 230 to 800 g / mol.
[0035] The viscosity (40° C.) of the branched polyglycerol is preferably from 5,000 to 35,000 mPa·s, and more preferably from 8,000 to 30,000 mPa·s.
[0036] The hydroxyl value of the branched polyglycerol is preferably 500 to 2,000 KOHmg / g, more preferably 800 to 1,200 KOHmg / g. The hydroxyl value can be calculated according to the 9th Edition of the Food Additives Standards "Testing Methods for Fats and Oils" or the Standard Fats and Oils Analysis Testing Method. The branched polyglycerol may be used alone or in combination of two or more kinds.
[0037] As the branched polyglycerol having a degree of polymerization of 10 or less, the following products available from Daicel Corporation can be used. The viscosity is measured at 40° C. using an E-type viscometer at a rotation speed of 1 to 5 rpm depending on the viscosity.
[0038] Product name PGL03P: Number average molecular weight = 240 g / mol, viscosity (40°C) = 8,300 mPa·s, hydroxyl value = 1,100 to 1,200 KOHmg / g Product name PGL06: Number average molecular weight = 460g / mol, viscosity (40℃) = 23,000mPa·s, hydroxyl value = 900~1,000KOHmg / g Product name PGL10: Number average molecular weight = 660 g / mol, viscosity (40°C) = 27,900 mPa·s, hydroxyl value = 800-900 KOHmg / g Product name PGL10PSW: Number average molecular weight = 780 g / mol, viscosity (40°C) = 16,800 mPa·s, hydroxyl value = 805-855 KOHmg / g
[0039] When the adhesive hydrogel of the present invention contains a branched polyglycerin having a degree of polymerization of 10 or less, the content of the branched polyglycerin in the adhesive hydrogel is not particularly limited, but from the viewpoint of the drying resistance of the adhesive hydrogel, it is preferably within the range of 5 to 80 parts by mass, more preferably within the range of 10 to 80 parts by mass, and more preferably within the range of 25 to 75 parts by mass, relative to the total amount of the polymer matrix, water, and polyhydric alcohol compound of 100 parts by mass, or relative to the total amount of the adhesive hydrogel. When the content of the branched polyglycerin is 5 parts by mass or more, it is preferable from the viewpoint of the drying resistance of the adhesive hydrogel. In addition, when the content is 80 parts by mass or less, it is preferable because the viscosity of the adhesive hydrogel composition is relatively low and easy to handle.
[0040] From the viewpoint of drying resistance of the adhesive hydrogel, the total amount of triglycerin and / or branched polyglycerin is preferably within the range of 20 to 80 parts by mass, more preferably within the range of 25 to 75 parts by mass, based on 100 parts by mass of the total of the polymer matrix, water, and polyhydric alcohol compound, or based on the total amount of the adhesive hydrogel.
[0041] Although the applicant does not wish to restrict the present invention to a specific hypothesis or theory, it is speculated that the mechanism by which triglycerin and / or branched polyglycerin having a degree of polymerization of 10 or less improves dryness resistance or moisture retention is that the OH groups of the polyglycerin molecule form hydrogen bonds with surrounding water molecules, attracting the water molecules to the polyglycerin molecule, thereby accumulating moisture, suppressing water evaporation, and preventing dryness.
[0042] In addition to the above, the polyhydric alcohol may further contain other polyhydric alcohols. As the other polyhydric alcohols, diols such as ethylene glycol, propylene glycol, butanediol, polyhydric alcohols such as glycerin, pentaerythritol, sorbitol, polyhydric alcohol condensates such as polyethylene glycol, polypropylene glycol, and polyhydric alcohol modified products such as polyoxyethylene glycerin can be used. These polyhydric alcohols may be used alone or in combination of two or more.
[0043] In terms of the drying resistance of the adhesive hydrogel, the amount of polyhydric alcohol other than triglycerin and / or branched polyglycerol having a degree of polymerization of 10 or less is preferably within the range of 0 to 60 parts by mass, and more preferably within the range of 0 to 50 parts by mass, per 100 parts by mass of the polymer matrix, water, and polyhydric alcohol compound combined, or per 100 parts by mass of the total amount of the adhesive hydrogel.
[0044] The total content of polyhydric alcohols in the adhesive hydrogel of the present invention (total content of linear polyglycerol, branched polyglycerol, and other polyhydric alcohols) is not particularly limited, but is preferably within the range of 30 to 80 parts by mass, more preferably within the range of 40 to 75 parts by mass, based on 100 parts by mass of the polymer matrix, water, and polyhydric alcohol compound, or based on the total amount of the adhesive hydrogel. When the content of polyhydric alcohols is 30 parts by mass or more, the gel is less likely to dry, and the gel has good stability over time and flexibility, which is preferable. In addition, when the content is 80 parts by mass or less, bleeding out of polyhydric alcohols from the gel is suppressed, which is preferable. Alternatively, the total amount of polyhydric alcohols of the present invention is preferably within the range of 30 to 80% by mass, more preferably within the range of 40 to 75% by mass, based on the total amount of the adhesive hydrogel.
[0045] (Polyphenol compounds) In this specification, the polyphenol compound refers to a compound having multiple hydroxyl groups bonded to a benzene ring. The polyphenol compound used in the present invention is a compound having hydroxyl groups bonded to each of two adjacent carbons forming at least one aromatic ring, and does not include the "polyhydric alcohol" used in the present invention.
[0046] Examples of polyphenol compounds include catechol, catechol derivatives (those in which a substituent other than hydrogen, such as an alkyl group, an aminoalkyl group, or a carboxyaminoalkyl group, is bonded to a carbon atom of the benzene ring other than the carbon to which the hydroxyl group of catechol is bonded, e.g., dopamine, 2,3-dihydroxybenzoic acid, 3,4-dihydroxybenzoic acid, and 3,4-dihydroxyphenylalanine), gallic acid, gallic acid esters (propyl ester, isoamyl ester, octyl ester, dodecyl ester, and the like), pyrogallol, phloroglycine, catechin, epicatechin, gallocatechin, catechin gallate, gallocatechin gallate, and epicatechin gallate. Examples of tannins that may be used include, but are not limited to, epigallocatechin gallate, epigallocatechin, glucogallin, proanthocyanidin and its polymers, flavones (e.g., rutin, quercetin, quercetagin, quercetagetin, gossypetin, etc.), ellagic acid, penta-O-galloylglucose, tannic acid, gallotannin (tannin extracted from peony root), geraniin (tannins extracted from geranium herb, Mallotus japonicus, pomegranate skin, Chinese cornus, Japanese elm, etc.), condensed tannins (tannins extracted from persimmon tannin, cinnamon bark, ash tree, Japanese elm, etc.), tannins extracted from Quercus salicina bark, Quercus mizunara bark, and nuts of the same tree.
[0047] Tannic acid is not particularly limited, but examples thereof include hamameli tannin, persimmon tannin, tea tannin, Chinese gall tannin, gall tannin, myrobalan tannin, dividivi tannin, algarovilla tannin, valonia tannin, catechin tannin, etc. Tannic acid may be a single compound or a mixture of two or more compounds. As the polyphenol compound, gallic acid esters and tannic acid are preferred, and tannic acid is more preferred.
[0048] The polyphenol compounds represented by the following formulas (1) to (6) are examples of the polyphenol compounds that can be used in the present invention. 1 , R 2 , R 3 , and R 4 are each independently hydrogen or a hydrocarbon group having 1 to 8 carbon atoms. 1 , and R 2 are each independently hydrogen or a hydrocarbon group having 1 to 8 carbon atoms. 1 is hydroxy or OR 2 and R 2 is a hydrocarbon group having 1 to 15 carbon atoms, and in formula (6), R 1 , R 2 , and R 3 are each independently hydrogen, hydroxy, or a hydrocarbon group having 1 to 8 carbon atoms. In a preferred embodiment, the hydrocarbon group in each of the formulas (1), (2), (4), and (6) is an alkyl group. The molecular weight of the condensed tannin of the formula (6) is, for example, 500 to 20,000.
[0049] [ka]
[0050] By using a polyphenol compound in which a hydroxyl group is bonded to each of two adjacent carbons that form at least one aromatic ring in an adhesive hydrogel, it is possible to impart high adhesive strength to the adhesive hydrogel in a high humidity environment.
[0051] The content of the polyphenol compound in the adhesive hydrogel of the present invention is not particularly limited, but is preferably within the range of 0.01 to 20 parts by mass, more preferably within the range of 0.1 to 10 parts by mass, and more preferably within the range of 1 to 5 parts by mass, based on 100 parts by mass of the polymer matrix, water, and polyhydric alcohol compound, or based on the total amount of the adhesive hydrogel. When the content of the polyphenol compound is 0.1 parts by mass or more, it is preferable in terms of maintaining the adhesive strength in a high humidity environment. In addition, when the content of the polyphenol compound is 10 parts by mass or less based on 100 parts by mass of the polymer matrix, water, and polyhydric alcohol compound, or based on the total amount of the adhesive hydrogel, it is preferable in terms of producing a hydrogel with high adhesive strength even in a high humidity environment and suppressing the polymerization inhibition action of the polyphenol compound on the monomer constituting the matrix.
[0052] The polyphenol compounds in the adhesive hydrogel include not only those in which the polyphenol compounds are dissolved in the adhesive hydrogel, but also those in which the polyphenol compounds are incorporated as part of the gel skeleton through hydrogen bonding between the OH groups of the polyphenol compounds and the NH2 groups of the polymers that make up the gel.
[0053] Although the applicant does not wish to restrict the present invention to any particular hypothesis or theory, the applicant speculates that the mechanism by which polyphenol compounds improve adhesion is primarily one of the following four: (1) the aromatic rings and hydroxyl groups contained in the molecules of the polyphenol compounds interact with the surface of the adhesive surface and are adsorbed to the surface; (2) adhesion is improved by hydrogen bonding or the like between functional groups on the adhesive surface and hydroxyl groups of the polyphenol compounds; (3) catechol groups are oxidized and converted to quinone groups, which react with functional groups on the adhesive surface and chemically bond to each other, thereby improving adhesion; or (4) the polyphenol compounds themselves act as surfactants, breaking down lipid membranes and improving adhesion.
[0054] Polyglycerin has more OH groups in one molecule than simple glycerin with a degree of polymerization of 1, and is structurally more likely to form aggregates; therefore, it is presumed to improve the adhesiveness of hydrogels more effectively than glycerin.
[0055] Furthermore, even if the adhesive hydrogel-producing composition and adhesive hydrogel do not completely follow the above-mentioned mechanism, they are included within the technical scope of the present invention as long as they satisfy the requirements specified in the present invention.
[0056] (Water-soluble polymer) In order to enhance the adhesive strength, the hydrogel may contain an amphiphilic polymer such as polyacrylic acid and / or its salt, if necessary. Examples of such amphiphilic polymers include copolymers of acrylic acid and methacrylic acid, and polymers containing N-alkylsulfonic acid acrylamide as a structural unit. Any of these may be used alone, or multiple types may be used in combination.
[0057] (electrolyte) The adhesive hydrogel of the present invention may contain an electrolyte, if necessary. By blending an electrolyte into the adhesive hydrogel, a conductive gel is obtained. In addition, the addition of an electrolyte to the adhesive hydrogel improves ionic conductivity. The adhesive hydrogel to which conductivity has been imparted can be suitably used as an adhesive hydrogel for bioelectrodes such as an electrode for electrocardiogram measurement, an electrode for low-frequency therapeutic devices, and various earth electrodes. When used as such an adhesive hydrogel for bioelectrodes, the adhesive hydrogel containing an electrolyte preferably has a resistivity within the range of 0.01 to 100 kΩ·cm.
[0058] The electrolyte is not particularly limited, and examples thereof include alkali metal halides such as sodium halide (e.g., sodium chloride), lithium halide, and potassium halide; alkaline earth metal halides such as magnesium halide and calcium halide; other metal halides; hypochlorite, chlorite, chlorate, perchlorate, sulfate, carbonate, nitrate, and phosphate of various metals; inorganic salts such as ammonium salts and various complex salts; salts of monovalent organic carboxylic acids such as acetic acid, benzoic acid, and lactic acid; salts of polyvalent organic carboxylic acids such as tartaric acid; monovalent or divalent or higher salts of polyvalent carboxylic acids such as phthalic acid, succinic acid, adipic acid, and citric acid; metal salts of organic acids such as sulfonic acid and amino acids; organic ammonium salts; salts of polymer electrolytes with poly(meth)acrylic acid, polyvinylsulfonic acid, poly-tert-butylacrylamide sulfonic acid, polyallylamine, and polyethyleneimine;
[0059] In addition, as the electrolyte, a substance may be used that is insoluble when blended into the adhesive hydrogel, and that has the property of dissolving in the adhesive hydrogel over time even if it is in a dispersed form during preparation of the blend liquid. Examples of such electrolytes include silicates, aluminates, metal oxides, hydroxides, etc. These may be used alone or in combination of two or more.
[0060] In the case of imparting electrical conductivity to the adhesive hydrogel of the present invention, the content of the electrolyte in the adhesive hydrogel is preferably within the range of 0.05 to 10 parts by mass, more preferably within the range of 0.1 to 5 parts by mass, based on 100 parts by mass of the total of the polymer matrix, water, and polyhydric alcohol compound, or based on the total amount of the adhesive hydrogel. The adhesive hydrogel containing water has inherent dielectric properties, and when combined with an electrode element to create an electrode, it has an electric capacity according to the thickness of the gel and the area of the electrode element. However, the impedance (Z) of the electrode is greatly affected by the electrolyte concentration, particularly in the low-frequency region below 1 kHz. When the content of the electrolyte in the adhesive hydrogel is 0.001 parts by mass or more, the impedance can be reduced, making it suitable for electrical conductivity applications. In addition, when the content of the electrolyte is 10 parts by mass or less, the electrolyte can be dissolved uniformly in the adhesive hydrogel, and crystal precipitation inside the gel or inhibition of dissolution of other components is unlikely to occur.
[0061] The electrolyte may be used for purposes other than imparting electrical conductivity to the adhesive hydrogel. For example, an acid salt, a base salt, a polyfunctional salt, or a base such as sodium hydroxide may be added for the purpose of adjusting the pH of the adhesive hydrogel. The electrolyte may also be added for the purpose of improving the moisture retention performance or imparting antibacterial properties to the adhesive hydrogel.
[0062] (Thickener) The adhesive hydrogel of the present invention may contain a thickener as necessary. By blending a thickener into the adhesive hydrogel, the viscosity of the hydrogel can be adjusted, and an adhesive hydrogel with high adhesive strength can be obtained. Examples of the thickener include organic thickeners such as polyacrylic thickeners, urethane thickeners, polyether thickeners, polyvinyl alcohols, and cellulose derivatives, and inorganic thickeners such as clay minerals. Examples of the inorganic thickener include clay minerals. Examples of the clay minerals include smectite clays such as bentonite, montmorillonite, saponite, beidellite, hectorite, stevensite, sauconite, and nontronite, natural clays such as vermiculite, halloysite, swelling mica, zeolite, and attapulgite, or synthetic clays. Only one type of thickener may be contained, or two or more types may be contained.
[0063] The content of the thickener in the adhesive hydrogel of the present invention is not particularly limited, but is preferably within the range of 1 to 10 parts by mass, and more preferably within the range of 2 to 10 parts by mass, per 100 parts by mass of the total of the polymer matrix, water, and polyhydric alcohol compound, or per 100 parts by mass of the total amount of the adhesive hydrogel.
[0064] (Other additives) The adhesive hydrogel may optionally contain other additives. Examples of other additives include preservatives, bactericides, antifungal agents, rust inhibitors, antioxidants, antifoaming agents, stabilizers, fragrances, surfactants, colorants, and medicinal ingredients (e.g., anti-inflammatory agents, vitamins, whitening agents, etc.). These additives may be used alone or in combination of two or more. These additives may be used within the range of 0.01 to 10 parts by mass relative to a total of 100 parts by mass of the polymer matrix, water, and polyhydric alcohol compound, or relative to the total amount of the adhesive hydrogel.
[0065] As described above, the adhesive hydrogel of the present invention has excellent drying resistance and high adhesive strength in high humidity environments by using triglycerol and / or branched polyglycerol with a degree of polymerization of 10 or less, and a polyphenol compound in which a hydroxyl group is bonded to each of two adjacent carbons that form at least one aromatic ring.
[0066] The thickness of the adhesive hydrogel of the present invention is not particularly limited, but may be a sheet having a thickness of 0.1 to 10 mm. The thickness is more preferably 0.3 to 5 mm. Such a sheet-shaped adhesive hydrogel having a thickness of 0.1 to 10 mm is excellent in flexibility and excellent in conformity to the surface of the skin of a living body.
[0067] <Method for manufacturing adhesive hydrogel> The adhesive hydrogel of the present invention can be easily produced by a production method in which a composition for producing an adhesive hydrogel, which comprises a monofunctional monomer, a crosslinkable monomer, water, a polyhydric alcohol, and the above-mentioned polyphenol compound, and the polyhydric alcohol comprises at least one of triglycerin and a branched polyglycerin having a polymerization degree of 10 or less, is used to copolymerize the monofunctional monomer and the crosslinkable monomer in the composition for producing an adhesive hydrogel. The composition for producing an adhesive hydrogel can contain the above-mentioned water-soluble polymer, electrolyte, thickener, and / or various additives as necessary.
[0068] The adhesive hydrogel of the present invention can also be produced by a production method in which a polymer matrix formed in advance, for example by polymerizing a monofunctional monomer and a crosslinkable monomer, is impregnated with water, a polyhydric alcohol containing triglycerin and / or a branched polyglycerin having a degree of polymerization of 10 or less, and the above-mentioned polyphenol compound, and, if necessary, the above-mentioned water-soluble polymer, electrolyte, thickener, and / or various additives.
[0069] The polymerization of the monofunctional monomer and the crosslinkable monomer is preferably carried out in the presence of a polymerization initiator. For example, it is preferable to include a polymerization initiator in the adhesive hydrogel-producing composition. The polymerization initiator is not particularly limited, and examples thereof include a thermal polymerization initiator and a photopolymerization initiator.
[0070] The thermal polymerization initiator is not particularly limited as long as it is cleaved by heat to generate radicals, and examples thereof include organic peroxides such as benzoyl peroxide; azo polymerization initiators such as azobiscyanovaleric acid, azobisisobutyronitrile, and azobisamidinopropane dihydrochloride; and persulfates such as potassium persulfate and ammonium persulfate. These thermal polymerization initiators may be used alone or in combination of two or more. If necessary, a redox initiator consisting of a reducing agent such as ferrous sulfate or pyrosulfite and a peroxide such as hydrogen peroxide, sodium thiosulfate, or peroxodisulfate may be used in combination with the thermal polymerization initiator.
[0071] The photopolymerization initiator is not particularly limited as long as it is cleaved by ultraviolet or visible light to generate radicals. Examples of the photopolymerization initiator include azo-based polymerization initiators such as 2,2'-azobis-N-(2-hydroxyethyl)propionamide and 2,2'-azobis(1-imino-1-pyrrolidino-2-methylpropane) dihydrochloride, α-hydroxyketones, α-aminoketones, benzyl methyl ketal, bisacylphosphine oxides, and metallocenes. More specifically, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-propan-1-one (product name: Omnirad (registered trademark) 2959, manufactured by IGM Resins BV), 2-hydroxy-2-methyl-1-phenyl-propan-1-one (product name: Omnirad (registered trademark) 1173, manufactured by IGM Resins BV), and the like. BV), 1-hydroxy-cyclohexyl-phenyl-ketone (product name: Omnirad (registered trademark) 184, IGM Resins BV), 2-methyl-1-[(methylthio)phenyl]-2-morpholinopropan-1-one (product name: Omnirad (registered trademark) 907, IGM Resins BV), 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one (product name: Omnirad (registered trademark) 369, IGM Resins BV). These photopolymerization initiators may be used alone or in combination of two or more.
[0072] The amount of the polymerization initiator used is preferably 0.01 to 1.0 parts by mass, more preferably 0.05 to 0.5 parts by mass, relative to 100 parts by mass of the total amount of the adhesive hydrogel-producing composition (total amount of the adhesive hydrogel obtained). When the amount is 0.01 part by mass or more, the polymerization reaction proceeds sufficiently, and the amount of the monofunctional monomer and the crosslinkable monomer remaining in the adhesive hydrogel obtained can be reduced. Also, when the amount is 1.0 part by mass or less, discoloration (yellowing) and odor caused by the polymerization initiator remaining in the adhesive hydrogel obtained can be prevented.
[0073] The method for polymerizing the monofunctional monomer and the crosslinkable monomer is not particularly limited, and examples thereof include a method of heating, irradiating, or irradiating a mixture containing a monofunctional monomer and a crosslinkable monomer (such as the above-mentioned adhesive hydrogel producing composition) with heat, light, or radiation. Specifically, examples of the method include a method of adding a thermal polymerization initiator as a polymerization initiator to the above-mentioned mixture and polymerizing the monofunctional monomer and the crosslinkable monomer in the above-mentioned mixture by heating; a method of adding a photopolymerization initiator as a polymerization initiator to the above-mentioned mixture and polymerizing the monofunctional monomer and the crosslinkable monomer in the above-mentioned mixture by light irradiation (ultraviolet or visible light irradiation); a method of adding a thermal polymerization initiator and a photopolymerization initiator as polymerization initiators to the above-mentioned mixture and polymerizing the monofunctional monomer and the crosslinkable monomer in the above-mentioned mixture by simultaneously irradiating and heating the mixture with light, and a method of irradiating the above-mentioned mixture with radiation such as an electron beam or gamma rays to polymerize the monofunctional monomer and the crosslinkable monomer in the above-mentioned mixture. In addition, when a redox initiator is used in combination as a thermal polymerization initiator, the reaction can be carried out without heating, but in order to reduce the amount of residual monomers or shorten the reaction time, it is preferable to heat the mixture even when a redox initiator is used in combination. As described above, it is also possible to irradiate the mixture with radiation to polymerize the monofunctional monomer and the crosslinkable monomer in the mixture, but since this requires special equipment for radiation irradiation, a method of heating or irradiating the mixture with light is preferable as a method of polymerizing the monofunctional monomer and the crosslinkable monomer in the mixture, and from the viewpoint of being able to obtain a gel with stable physical properties, a method of irradiating the mixture with light is more preferable.
[0074] When the mixture contains a photopolymerization initiator and is polymerized by ultraviolet irradiation, the cumulative dose of ultraviolet light is 1000 mJ / cm. 2 More preferably, it is equal to or greater than this. In addition, when producing the adhesive hydrogel of the present invention, the content of components other than the monofunctional monomer and the crosslinkable monomer (e.g., polyhydric alcohol, water, polyphenol compound, water-soluble polymer, electrolyte, thickener, other additives, etc.) relative to the total mass of the components (e.g., monofunctional monomer, crosslinkable monomer, polyhydric alcohol, water, polyphenol compound, water-soluble polymer, electrolyte, thickener, other additives, etc.) used in the production of the adhesive hydrogel (or the total mass of the composition for producing the adhesive hydrogel) is equal to the content of components other than the structural units derived from the monofunctional monomer and crosslinkable monomer in the adhesive hydrogel of the present invention. In addition, the content of the monofunctional monomer and the crosslinkable monomer relative to the total mass of the components (or the total mass of the composition for producing the adhesive hydrogel) used in the production of the adhesive hydrogel is equal to the content of the structural units derived from the monofunctional monomer and the crosslinkable monomer in the adhesive hydrogel of the present invention. For example, the content of the monofunctional monomer in the adhesive hydrogel-producing composition is equal to the content of the structural unit derived from the monofunctional monomer in the adhesive hydrogel of the present invention. Also, the content of the crosslinkable monomer in the adhesive hydrogel-producing composition is equal to the content of the structural unit derived from the crosslinkable monomer in the adhesive hydrogel of the present invention. Furthermore, the total content of the monofunctional monomer and the crosslinkable monomer in the adhesive hydrogel-producing composition is equal to the content of the polymer matrix in the adhesive hydrogel of the present invention.
[0075] <Adhesive hydrogel sheet> The adhesive hydrogel of the present invention is prepared, for example, by gelling a liquid adhesive hydrogel-producing composition through polymerization and crosslinking, and therefore can be appropriately shaped according to the application.
[0076] 1 shows a cross section of one embodiment of a gel sheet containing an adhesive hydrogel according to the present invention. In the gel sheet 1 of this embodiment, a base film 3 and a top film 4 for protecting the adhesive hydrogel 2 are laminated on both sides of a sheet-like adhesive hydrogel 2. The thickness of the adhesive hydrogel 2 can be appropriately set depending on the application of the gel sheet 1, but for example, when the gel sheet 1 is used by adhering it to a living body, the thickness of the adhesive hydrogel 2 is preferably set within the range of 0.01 mm to 2.0 mm.
[0077] As the base film 3, for example, a resin film made of a resin such as polyester (e.g., polyethylene terephthalate (PET)), polyolefin (e.g., polypropylene), polystyrene, polyurethane, or the like, paper, or paper laminated with a resin film can be used. The surface of the base film 3 that comes into contact with the adhesive hydrogel 2 is preferably subjected to a release treatment such as silicone coating. That is, when the base film 3 is used as a release paper, a film obtained by subjecting the surface of a resin film made of a resin (e.g., polyester, polyolefin, polystyrene, or the like), paper, or paper laminated with the resin film to a release treatment can be suitably used as the base film 3. A biaxially oriented PET film, a biaxially oriented polypropylene (OPP) film, or the like is particularly preferred as the base film to be subjected to the release treatment. As a method of release treatment, silicone coating can be mentioned, and in particular, a baked type silicone coating that crosslinks and hardens with heat or ultraviolet light is preferred.
[0078] Although it is possible to use a film made of the same material as the base film 3 as the top film 4, it is preferable to select a film made of a material that does not block light so as not to interfere with photopolymerization. Also, it is preferable not to use a film used as a backing material (lining material) as the top film 4. In particular, if there is a possibility that the film used as the backing material may deteriorate due to exposure to ultraviolet rays or the like, using the film used as the backing material as the top film 4 is not preferable, because the film used as the backing material will be located on the side directly exposed to ultraviolet rays.
[0079] In this embodiment, an intermediate substrate 5 made of woven or nonwoven fabric is embedded along the surface direction of the adhesive hydrogel 2 in order to improve the tear strength and handling of the adhesive hydrogel 2. The material of the woven or nonwoven fabric may be natural fibers such as cellulose, silk, or hemp, or synthetic fibers such as polyester, nylon, rayon, polyethylene, polypropylene, or polyurethane, or a blend thereof, and a binder may be used as necessary, and further, coloring may be performed as necessary. The intermediate substrate 5 may be omitted.
[0080] The manufacturing method of the nonwoven fabric is not particularly limited, but examples thereof include a dry method, a wet method, a spunbond method, a meltblown method, an airlaid method, a chemical bond method, a thermal bond method, a needle punch method, and a hydroentanglement method. It is more preferable to adopt a manufacturing method according to the basis weight and material, and to have no unevenness in the basis weight, in order to control the position of the intermediate substrate 40. The woven fabric is also not particularly limited, and can be selected as appropriate, such as plain weave, tricot, or raschel.
[0081] The basis weight of the woven or nonwoven fabric is not particularly limited as long as it is a basis weight that can provide the desired physical properties as the intermediate substrate 5. For example, it is 10 to 40 g / m 2 It is preferable that the range is 10 to 28 g / m 2 It is more preferable that the basis weight is 10 g / m 2If the weight is 40 g / m or more, the adhesive hydrogel 2 can be sufficiently reinforced, and unevenness in the weight permeation can be suppressed, so that the liquid permeates uniformly during the production of the adhesive hydrogel 2 and the positional fluctuation of the intermediate substrate 5 can be suppressed, which is preferable. 2 If the thickness is less than this, the intermediate base material 5 does not become too hard, and the adhesive hydrogel 2 has good conformability to the skin, which is preferable.
[0082] The thickness of the intermediate substrate 5 is preferably within a range of 0.05 to 2.0 mm. Also, 0.05 to 0.5 mm is more preferable, and 0.08 to 0.3 mm is particularly preferable. If it is 0.05 mm or more, the adhesive hydrogel 2 can be sufficiently reinforced and unevenness in basis weight is suppressed, so that the liquid permeates uniformly during the production of the adhesive hydrogel 2 and the positional fluctuation of the intermediate substrate 5 is suppressed, which is preferable. If it is 2.0 mm or less, the liquid permeability is good, which is preferable.
[0083] The manufacturing method of the gel sheet 1 is not particularly limited, and the conditions vary depending on the composition of the adhesive hydrogel 2, the material and thickness of the intermediate substrate 5, etc. For example, a method of holding the intermediate substrate 5 on the upper side of the base film 3 while applying a certain tension to the intermediate substrate 5, pouring a gel composition containing a mixture of the various components onto the upper and lower sides of the intermediate substrate 5, covering it with a top film 4, and crosslinking and curing the adhesive hydrogel 2 by light irradiation and / or heat to obtain the gel sheet 1, a method of producing two adhesive hydrogels with a smooth surface, sandwiching the intermediate substrate 5, which is held under a certain tension, between these adhesive hydrogels, and further laminating the base film 3 and the top film 4 on both sides to obtain the gel sheet 1, and the like can be appropriately adopted.
[0084] <Applications of adhesive hydrogel> The adhesive hydrogel of the present invention as described above is inhibited from swelling due to the intrusion of moisture from the outside, and can maintain its initial high adhesive strength even in a high humidity environment. Therefore, it has resistance to sweat and the like, and can be suitably used as an adhesive hydrogel for a gel member to be attached to the surface of a living body in a living body electrode, or for an adhesive hydrogel for a medical external material to be attached to a living body, such as various adhesive tapes and wound dressings.
[0085] (Bioelectrodes) According to one aspect of the present invention, a biological electrode containing the adhesive hydrogel is provided. The biological electrode may be an electrode in which the adhesive hydrogel and an electrode made of a conductive material are laminated. The electrode may contain a conductive material. Examples of such materials include metals such as aluminum, stainless steel, copper, platinum, silver, a silver-silver chloride complex, gold, tin, titanium, nickel, and molybdenum, conductive carbon materials such as carbon black and graphite, and mixtures thereof.
[0086] The biological electrode of this embodiment can be used as a bioelectric potential measurement electrode used for electrocardiograms, electroencephalograms, nystagmus, electromyograms, etc., an electrical stimulation electrode used for transcutaneous electrical stimulation therapy (TENS), low-frequency treatment, etc., a counter electrode for an electric scalpel, an electrode for iontophoresis, or other medical electrodes.
[0087] (Medical topical materials) According to one aspect of the present invention, there is provided a medical topical material comprising a support and the above-mentioned adhesive hydrogel provided on at least one surface of the support. The medical topical material of this embodiment is prepared by (i) applying the adhesive hydrogel-producing composition to one or both sides of a support, and polymerizing and crosslinking the composition, (ii) directly attaching the adhesive hydrogel to one or both sides of a support, (iii) applying the adhesive hydrogel-producing composition onto release paper, and polymerizing and crosslinking the composition, and then attaching the composition to a support, or (iv) attaching the adhesive hydrogel attached to the release paper to a support. The adhesive hydrogel may be in the form of a sheet.
[0088] The support is not particularly limited as long as it is capable of holding the adhesive hydrogel. Specific examples include film or sheet-like supports used in bandages, adhesive dressings, or poultices, and these may be porous or non-porous.
[0089] The raw material of the support may be, for example, polyurethane, polyethylene, ethylene-vinyl acetate copolymer, ethylene-acrylic acid ester copolymer, polyvinyl chloride, unplasticized soft polyvinyl chloride (e.g., internal copolymer or blend system), polypropylene, nylon, polyester, silicone rubber, foamed polyethylene, foamed polyurethane, foamed ethylene-vinyl acetate copolymer, or other synthetic resin, or metals such as aluminum and copper, formed into a film or sheet. In addition, paper, nonwoven fabric, woven fabric, mesh fabric, or the like made of natural or synthetic fibers (e.g., regenerated cellulose (e.g., rayon), cellulose ester, or the like) may also be used, and a breathable or non-breathable substrate may be appropriately selected depending on the purpose. In addition, the above-mentioned films, metal films or sheets, woven fabric, or the like may be appropriately combined and laminated to form a laminate support. For example, examples of laminate supports include, but are not limited to, polyethylene-rayon laminated paper, PET and aluminum laminate, polyurethane and rayon laminate, and the like.
[0090] The thickness of the support which is a film or sheet (the total thickness in the case of a laminate) is not particularly limited, but can be, for example, 5 to 300 μm, and preferably 10 to 100 μm.
[0091] A surface treatment layer may be provided between the support and the adhesive hydrogel in order to enhance the adhesion between the support and the adhesive hydrogel. Specific examples of the surface treatment layer include physical surface treatments such as corona discharge treatment, plasma treatment, ozone treatment, ultraviolet irradiation treatment, and flame treatment, and surface treatments using coating agents such as silane coupling treatment, anchor coat, and primer coat, or combinations thereof.
[0092] The surface of the support is subjected to a surface treatment, and the adhesive hydrogel-producing composition is directly applied onto the resulting surface-treated layer and polymerized, thereby firmly adhering the support and the adhesive hydrogel. By providing a support to the medical topical material, the medical topical material can be used as a surgical tape.
[0093] An example of a medical topical material is shown in Figure 2. The medical topical material 6 comprises a support 7 and an adhesive hydrogel 8 provided in contact with one side of the support 7. The side of the adhesive hydrogel 8 opposite to the side in contact with the support 7 is attached to the skin 9 of a user of the medical topical material 6. As described above, a surface treatment layer may be provided between the support 7 and the adhesive hydrogel 8.
[0094] The adhesive hydrogels and medical topical materials of the above-mentioned embodiments can be suitably used as adhesive materials to be attached to a living body, such as surgical tapes to be attached to a living body, tapes for fixing catheters and infusion tubes / electrocardiogram electrodes / other sensors, poultices, wound dressings, tapes for fixing artificial anuses, etc., adhesive materials for fixing leads for electric therapy devices / magnetic therapy devices, and carrier / adhesive materials for transdermal absorption agents, or industrial adhesive materials for building materials / electronic materials, etc.
[0095] The disclosures of all patent applications and publications cited herein are hereby incorporated by reference in their entireties. The following examples are intended for illustrative purposes only and are not intended to limit the scope of the present invention in any way. Unless otherwise specified, reagents are commercially available or are obtained or prepared according to conventional techniques or procedures known in the art. EXAMPLES
[0096] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. 1.Materials used Acrylamide MBAA: N,N'-methylenebisacrylamide PGL X: Polyglycerin with branched structure, manufactured by Daicel Corporation, degree of polymerization 40, purity 90% Concentrated glycerin: Linear polyglycerin, polymerization degree 1, 100% pure, manufactured by Sakamoto Pharmaceutical Co., Ltd. Triglycerin: Linear polyglycerin, polymerization degree 3, manufactured by Sakamoto Pharmaceutical Co., Ltd. Unigly G-6: Linear polyglycerin, polymerization degree 6, purity 90%, NOF Corporation Polyglycerin #750: Linear polyglycerin, degree of polymerization 10, purity 90%, manufactured by Sakamoto Pharmaceutical Co., Ltd. PGL 06: Polyglycerin with branched structure, polymerization degree 6, 100% pure, manufactured by Daicel Corporation PGL 10PSW R: Polyglycerin with branched structure, polymerization degree 10, purity 95%, manufactured by Daicel Corporation PGL 20PW: Polyglycerin with branched structure, polymerization degree 20, purity 90%, manufactured by Daicel Corporation PGL X: Polyglycerin with branched structure, polymerization degree 40, purity 90%, manufactured by Daicel Corporation Tannic acid Ethyl gallate Catechol ·Jurimer AC-20H: Polyacrylic thickener Toagosei Co., Ltd. Omnirad 2959: Photoinitiator, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-propan-1-one, IGM Resins BV
[0097] 2. Preparation of Gel Examples 1 to 4, Comparative Examples 1 to 7 A gel was produced using the composition shown in Table 1 according to the following procedure. Acrylamide was used as a polymerizable monomer, N,N'-methylenebisacrylamide (MBAA) was used as a crosslinkable monomer, a polyphenol compound was used as an adhesive, triglycerin or polyglycerin was used as a polyhydric alcohol, and water was used as a solvent in a plastic container, and the mixture was dissolved and stirred to obtain a composition for producing an adhesive hydrogel.
[0098] Next, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-propan-1-one (trade name Omnirad2959, manufactured by IGM Resins BV) was added as a photopolymerization initiator to the mixture, and the mixture was further stirred and dissolved.
[0099] Next, a nonwoven fabric (R004, Shinwa Co., Ltd., 65mm x 90mm) was laid in a silicone rubber mold (70mm x 100mm, thickness 1.0mm) on a 38μm thick biaxially stretched polyester film that had been siliconized and placed on glass, and the composition was poured in. A 38μm thick biaxially stretched polyester film that had been siliconized was placed on the mold so as not to trap air bubbles, and quartz glass was placed on top to control the thickness. This was measured with a peak intensity of 95mW / cm 2 The gel was irradiated with ultraviolet light from a UV lamp for 60 seconds, and removed from the mold to prepare a sample for evaluation. A sample for measuring the water loss rate was prepared in the same manner, but without the nonwoven fabric. The evaluation results of the obtained samples are shown in Table 1.
[0100] 3. Evaluation of Adhesive Hydrogels
[0101] (1) Adhesive strength (I) Initial adhesion The 90° adhesive strength was measured by the following method. The hydrogels (gel sheets) with a thickness of 1.0 mm obtained in Examples 1 to 4 and Comparative Examples 1 to 7 were each cut into a rectangular shape with a width of 20 mm and a length of 90 mm, and then the protective film on one side was peeled off and peach-coated paper was attached. Thereafter, the protective film on the other side was peeled off and the sheet was attached to a SUS plate with a thickness of 0.8 mm, a length of 150 mm and a width of 25 mm, and then rolled back and forth once with a 2 kg roller, and then set in a texture analyzer (manufactured by Eiko Seiki Co., Ltd., device name: Texture Analyzer TA.XT Plus). After this, in accordance with JIS Z 0237:2009, the peel strength when peeled in the 90° direction at a speed of 300 mm / min with the length direction of the sample set to 0° was measured as the adhesive strength. The load applied when peeling the test piece in a 90° direction at a speed of 300 mm / min in an environment of 23°C and relative humidity of 55% was measured, and the measured load (N / 20 mm) was taken as the initial adhesive strength. Pass: Initial adhesive strength is 10 (N / 20mm) or more. Fail: The initial adhesive strength is less than 10 (N / 20mm).
[0102] (II) Adhesion strength after exposure to high temperatures In addition, the PET film was removed from the above test piece, and the hydrogel was left to stand in a thermostatic chamber at 40°C and a relative humidity of 90% for 24 hours. The hydrogel was then similarly attached to a SUS plate, and the load applied when peeling the test piece in a 90° direction at a speed of 300 mm / min in an environment of 23°C and a relative humidity of 55% in accordance with JIS Z0237:2009 was measured, and the measured load was regarded as the adhesive strength after exposure to a high humidity environment. Pass: Adhesive strength after exposure to high humidity is 1.5 (N / 20mm) or more. Fail: Adhesive strength after exposure to high humidity is less than 1.5 (N / 20mm).
[0103] (III) Moisture-resistant adhesion improvement rate Hydrogels without tannic acid and hydrogels with 1% by mass of tannic acid were prepared according to the formulations of the respective examples and comparative examples, and the adhesive strength of each was measured after exposure to a high humidity environment. The moisture-resistant adhesion improvement rate due to the addition of tannic acid was calculated using the following formula. Samples without tannic acid were marked with "-". Moisture resistance adhesion improvement rate (%) = F1 / F0 × 100 F0 = Adhesive strength of hydrogel composited with 1% by mass of tannic acid after exposure to a high humidity environment F1 = Adhesive strength of hydrogel without tannic acid after exposure to a high humidity environment Pass: Moisture resistance adhesion improvement rate is 120% or more. Fail: The moisture resistance adhesion improvement rate is less than 120%.
[0104] (2) Moisture runoff rate The hydrogel was cut into a 40 mm square and its weight (g) was measured in advance. It was then dried in an oven at 120°C for 120 minutes, after which its weight (g) was measured. The loss rate of water present in the hydrogel was calculated (G0) using the following formula. Water loss rate (G0) (%) = (gel weight - gel weight after drying) / gel weight × 100 Pass: Water loss rate (G0) is 20% or less. Fail: Water loss rate (G0) is higher than 20%.
[0105] 4.Results The samples of Examples 1 to 3 (composite formulation of triglycerin or branched polyglycerin having a degree of polymerization of 10 or less and tannic acid) passed the initial adhesive strength, adhesive strength after exposure to high temperature, moisture-resistant adhesion improvement rate, and water outflow rate. It was also confirmed that all evaluation items were passed for Example 4 (composite formulation of branched polyglycerin having a degree of polymerization of 10 or less and ethyl gallate). In contrast, Comparative Examples 1 and 2, which are samples that do not contain polyphenol compounds, failed at least one of the adhesive strength and moisture loss rate, Comparative Example 3, in which the polyhydric alcohol is concentrated glycerin (degree of polymerization is 1), failed both the adhesive strength and the moisture loss rate, Comparative Examples 4 and 5, which contain a linear polyglycerin with a degree of polymerization of more than 3, failed both the initial adhesive strength and the moisture-resistant adhesion improvement rate, and Comparative Examples 6 and 7, which contain a branched polyglycerin with a degree of polymerization of more than 10, failed both the adhesive strength and the moisture loss rate. [Explanation of symbols]
[0106] 1. Gel sheet 2. Adhesive hydrogel 3...Base film 4…Top film 5...Intermediate substrate 6. Medical topical materials 7...Support 8...Adhesive hydrogel 9…Skin
[0107]
Table 1
Claims
1. An adhesive hydrogel comprising a polymer matrix made of a copolymer of a monofunctional monomer and a crosslinkable monomer, water, a polyhydric alcohol, and a polyphenol compound, The polyhydric alcohol contains triglycerin and / or a branched polyglycerin having a degree of polymerization of 10 or less, An adhesive hydrogel, wherein the polyphenol compound is a compound having a hydroxyl group bonded to each of two adjacent carbons forming at least one aromatic ring.
2. The adhesive hydrogel according to claim 1 , wherein the polyhydric alcohol comprises a branched polyglycerol having a degree of polymerization of 10 or less.
3. The adhesive hydrogel according to claim 1 , wherein the monofunctional monomer comprises an acrylamide monomer.
4. The adhesive hydrogel according to claim 1 , wherein the amount of the polyphenol compound is 10 parts by mass or less per 100 parts by mass of the total of the polymer matrix, water, and polyhydric alcohol.
5. The adhesive hydrogel of claim 1 , further comprising an electrolyte.
6. A gel sheet comprising the adhesive hydrogel according to any one of claims 1 to 5.
7. A biological electrode comprising the adhesive hydrogel according to any one of claims 1 to 5.
8. A medical external use material comprising a support and the adhesive hydrogel according to any one of claims 1 to 5 provided on at least one surface of the support.
9. A composition for producing an adhesive hydrogel, comprising a monofunctional monomer, a crosslinkable monomer, water, a polyhydric alcohol, and a polyphenol, wherein the polyhydric alcohol comprises triglycerin and / or a branched polyglycerin having a degree of polymerization of 10 or less, and the polyphenol compound is a compound having a hydroxyl group bonded to each of two adjacent carbons forming at least one aromatic ring.
Citation Information
Patent Citations
Wireless communication device, wireless communication system, connection processing method, and connection processing program
JP6663110B2
Hydrogel
JP7037639B2